2013
DOI: 10.1152/jn.01055.2012
|View full text |Cite
|
Sign up to set email alerts
|

Integration of texture and disparity cues to surface slant in dorsal visual cortex

Abstract: Reliable estimation of three-dimensional (3D) surface orientation is critical for recognizing and interacting with complex 3D objects in our environment. Human observers maximize the reliability of their estimates of surface slant by integrating multiple depth cues. Texture and binocular disparity are two such cues, but they are qualitatively very different. Existing evidence suggests that representations of surface tilt from each of these cues coincide at the single-neuron level in higher cortical areas. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 99 publications
5
57
0
Order By: Relevance
“…If normalization does occur, then during engagement with symmetry we would expect to see greater feedback to e.g. V3 (for slanted compared to frontoparallel symmetry) from visual areas known to compute slant (Murphy, Ban, & Welchman, 2013; Tsutsui et al, 2001). However, if retinal structure is sufficient to extract symmetry from slanted planes then we would expect similar feedforward and feedback processes to be invoked independent of stimulus slant and task.…”
Section: Discussionmentioning
confidence: 99%
“…If normalization does occur, then during engagement with symmetry we would expect to see greater feedback to e.g. V3 (for slanted compared to frontoparallel symmetry) from visual areas known to compute slant (Murphy, Ban, & Welchman, 2013; Tsutsui et al, 2001). However, if retinal structure is sufficient to extract symmetry from slanted planes then we would expect similar feedforward and feedback processes to be invoked independent of stimulus slant and task.…”
Section: Discussionmentioning
confidence: 99%
“…Most have focused on non-spatial aspects of depth, e.g., neural representations of 3D object structure (Backus et al, 2001; Durand et al, 2009), or the integration of different depth cues (Ban et al., 2012; Dekker et al, 2015; Murphy et al, 2013; Welchman et al, 2005), although a few recent studies have examined fMRI sensitivity to differences in depth from disparity, finding regions that are sensitive to absolute vs relative (Neri et al, 2004) or metric vs categorical (Preston et al, 2008) depth differences. Neurophysiology studies have also reported neurons with different depth preferences in various visual areas (DeAngelis & Newsome, 1999; Hubel et al, 2015; Tsao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while binocular disparity signals are found as early as V1, these signals are not thought to correspond to perception of depth until later visual areas (Barendregt, Harvey, Rokers, & Dumoulin, 2015; Cumming & Parker, 1997, 1999; Preston et al, 2008). These later visual areas (including V3A, V3B, V7, IPS, MT+, LO) have been shown to be sensitive to 3D object structure (Backus et al, 2001; Durand et al, 2009), differences in perceived depth (Neri et al, 2004; Preston et al, 2008), and the integration of different depth cues (Ban et al, 2012; Dekker et al, 2015; Murphy, Ban, & Welchman, 2013; Welchman et al., 2005). However, the nature of position-in-depth (spatial) representations remains less explored.…”
mentioning
confidence: 99%
“…Furthermore, temporary inactivation of area CIP in monkeys leads to impairments in perceiving depth structure and 3-D curvature, attesting to its critical role in representing those 3-D object properties (Van Dromme, Premereur, Verhoef, Vanduffel, & Janssen, 2016). Other studies suggest that CIP may also be a locus where different types of depth cues are integrated (Ban, Preston, Meeson, & Welchman, 2012; Murphy, Ban, & Welchman, 2013; Tsutsui, Jiang, Yara, Sakata, & Taira, 2001). CIP may be part of a larger object-processing network.…”
Section: Hallmarks Of Object-related Representations In Dorsal Cortexmentioning
confidence: 99%